Conection between Educative, Technological, Social and Economical dimensions in a group of nations with high and average human development - Pacheco Lay, Gonzalo Alberto (2014)
This investigation connects relative indicators in four systems: Educational, technological, social and economical systems. The information corresponds to transversal data from 39 countries, ranked in high and average human development. After using the correlation matrix and the dispersion diagram, the results reveal that, first of all, Professional indicators in research and development (R+D), 20% richer regarding the 20% poorer, are potentially useful for future studies about factors associated to academic performance in mathematics; and, second, Latin American countries (Argentina, Brazil, Chile, Mexico and Peru), independently of its location in the ranking of the human development, constitute an opposed group to most of the remaining countries when they are observed in the dispersion diagram.